Interpretazione e improvvisazione nell’estetica della formatività di Luigi Pareyson (Itinera, 2015)
The paper discusses the so-called “theory of formativity” developed by the existential philosopher Luigi Pareyson in his 1954 book “Estetica. Teoria della formatività” and other coeval essays based on aesthetics. In particular, it focuses on the above mentioned theory by exploring two closely-linked concepts: “improvisation” and “interpretation”, showing their profound liaison, especially from an aesthetic, hermeneutical and ontological point of view. In fact, Pareyson's theory of formativity can be described as “metaphysics of figuration”, “hermeneutics of art” and original relationship to being and truth.